A request to oblige the opponent to submit documents in his possession according to the Jordanian Evidence Law (Journal of the College of Basic Education, 2022)
This research talks about a request to oblige the opponent to submit a document in his hand, after which he has a means of proof, which plays an important role in persuading the judge and forming his belief and as a result the ruling on the subject matter of the case, which constitutes an exception to the general principle, which stipulates that the opponent may not be obligated to provide evidence against himself, unless Among the cases mentioned by the Jordanian legislator in Article (20) of the Jordanian Evidence Law exclusively, which are represented in two cases: if the law permits his request to submit or hand it over, and if his opponent relied on it at any stage of the lawsuit in accordance with the conditions and procedures specified by the law, and the Jordanian legislator mentioned this exception in order to achieve justice And its good conduct and not to cover up the facts and hide its features.